2017
DOI: 10.1128/jvi.01532-17
|View full text |Cite
|
Sign up to set email alerts
|

Full-Length Isoforms of Kaposi's Sarcoma-Associated Herpesvirus Latency-Associated Nuclear Antigen Accumulate in the Cytoplasm of Cells Undergoing the Lytic Cycle of Replication

Abstract: The latency-associated nuclear antigen (LANA) of the Kaposi's sarcomaassociated herpesvirus (KSHV) performs a variety of functions to establish and maintain KSHV latency. During latency, LANA localizes to discrete punctate spots in the nucleus, where it tethers viral episomes to cellular chromatin and interacts with nuclear components to regulate cellular and viral gene expression. Using highly sensitive tyramide signal amplification, we determined that LANA localizes to the cytoplasm in different cell types u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 114 publications
(167 reference statements)
1
7
0
Order By: Relevance
“…All the major LANA isoforms were observed in the samples; importantly, there are less LANA proteins expressed in the active CC9-LANA than in the mock-and inactive CC9-LANA-transduced cells (Fig. 6D) (47). These results demonstrated that Ad-CC9-LANA can indeed reduce KSHV latency by decreasing the number of KSHV episome in latently infected cells overtime.…”
Section: Resultsmentioning
confidence: 70%
“…All the major LANA isoforms were observed in the samples; importantly, there are less LANA proteins expressed in the active CC9-LANA than in the mock-and inactive CC9-LANA-transduced cells (Fig. 6D) (47). These results demonstrated that Ad-CC9-LANA can indeed reduce KSHV latency by decreasing the number of KSHV episome in latently infected cells overtime.…”
Section: Resultsmentioning
confidence: 70%
“…Confocal imaging suggests that the lytic replication compartments are two-dimensional rings and not cross sections of globular spheres. KSHV replication compartments have been described in other studies [ 57 60 ]. Replication compartments similar to what we observed have been described and shown to colocalize with DNA damage repair factors associate with NHEJ, including DNA-PK, ATM, and MRN components [ 57 ].…”
Section: Discussionmentioning
confidence: 77%
“…We observed rare punctate colocalization of KSHV lytic replication protein K8 with LANA rings, suggesting that these structures may be distinct from classical replication compartments described for other viruses. LANA has also been reported to accumulated in cytoplasmic foci during lytic replication cycle [ 60 ], but our experimental system using RFP-LANA may only observe full length LANA in the nucleus. While LANA is well known for its role in KSHV latent cycle replication, our new findings suggest that LANA also contributes to the structural organization of KSHV lytic cycle DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the relationships between KSHV infected cells and TIIC, we first defined 'infected cells' as those evincing a punctate nuclear KSHV LANA staining pattern by IHC [20]. LANA is responsible for maintaining the KSHV episome in infected cells during latency and is also expressed in lytic reactivation [21].…”
Section: Heterogeneous Expression Of Lana In Ks Biopsiesmentioning
confidence: 99%